Next generation access networks (NGANs) and the geographical segmentation of markets - Pereira, João Paulo (2011)
Telecom infrastructures are facing unprecedented challenges with increasing demands on network capacity. Next Generation Networks (NGN) allows consumers to choose between different access network technologies to access their service environment. The arrival of NGAN (Next Generation Access Network) has implications for the competitive conditions in access markets that are still uncertain (for example: access to ducts, dark fiber, equipment, etc.). The definition of the access price is a critical question, particularly when the incumbent also has activity in the retail market. In some regions, the regulatory authorities need to define the max price for wholesale access. In this context, the paper is divided into two main parts: 1) First we make a review of the main broadband access technologies (NGANs), and we propose a techno-economic model to support the new requirements of fixed and nomadic users. 2) In the 2nd part we propose a tool, developed in c language, which simulates the impact of retail and wholesale services prices variation in the provider’s profit, consumer surplus, welfare, etc.